CA19-9-Low&Lewis (+) pancreatic cancer: A unique subtype. (28th January 2017) - Luo, Guopei; Liu, Chen; Guo, Meng; Long, Jiang; Liu, Zuqiang; Xiao, Zhiwen; Jin, Kaizhou; Cheng, He; Lu, Yu; Ni, Quanxing; Yu, Xianjun
Abstract: The study was performed to identify unique subtype from the long-term survival (>24 months) patients with advanced pancreatic cancer (1039 cases). Long-term survival patients had higher proportion of low secretion of carbohydrate antigen 19-9 (CA19-9) than that of patients with non long-term survival (P < 0.001). Considering the impact of Lewis status on CA19-9 secretion, Lewis genotypes were further determined by Sanger sequencing. The prognosis of CA19-9-Low&Lewis (−) patients was worse than that of CA19-9-Low&Lewis (+) (hazard ratio (HR) = 0.37, P < 0.001). The proportion of epidermal growth factor receptor (EGFR) (−) cases was lower in the CA19-9-Low&Lewis (+) subgroup than that in other patients (P = 0.047). For the CA19-9-Low&Lewis (+) subgroup, chemotherapy plus radiotherapy but not chemotherapy was found to be an independent prognostic factor (versus best supportive care, chemotherapy, HR = 0.71, P = 0.267; chemotherapy plus radiotherapy, HR = 0.33, P = 0.022). We conclude that CA19-9-Low&Lewis (+) pancreatic cancer is a unique subtype with special biological properties. Highlights: Long-term survival patients had higher proportion of CA19-9 low-secretion (CA19-9 normal) than that of patients with non long-term survival. The prognosis of CA19-9-Low&Lewis (−) patients was worse than that of CA19-9-Low&Lewis (+). For the CA19-9-Low&Lewis (+) subgroup, chemotherapy plus radiotherapy but not chemotherapy was found to be an independent prognostic factor.